Assessment of a Parent-Child Interaction Intervention for Language Development in Children - Christakis, Dimitri A. (JAMA Netw Open, 2019)
IMPORTANCE: Parent-child interactions are critical for language development in early life. OBJECTIVE: To test whether a clinic-based intervention was associated with improved home language environment and language development. DESIGN, SETTING, AND PARTICIPANTS: A pre-post study of a multifaceted clinic-based intervention called Talk It Up was conducted for 61 English- or Spanish-speaking families with children aged 2 to 12 months. Enrollment took place at a single urban pediatric clinic from January to November 2017, with follow-up data collection through May 2018. Analyses took place from June to August 2018. INTERVENTIONS: The 6-month multifaceted intervention consisted of delivering Language Environment Analysis word counts with clinician feedback, coaching, and twice-weekly pushes of brief instructional videos via a commercially available smartphone application. MAIN OUTCOMES AND MEASURES: Baseline and follow-up z scores for adult word counts, parent-child conversational turns, and child vocalizations and language development as measured by the Developmental Snapshot score were compared and adjusted for confounders. RESULTS: Among 61 families, the mean (SD) child’s age at baseline was 5.9 (3.3) months. English was the primary language spoken in the home for 54 families (89%). At follow-up, Talk It Up was associated with significant improvements in adult word counts (mean z score, 0.30; 95% CI, 0.05-0.55), parent-child conversational turns (mean z score, 0.29; 95% CI, 0.002-0.59), and Developmental Snapshot score (mean, 6.59; 95% CI, 0.95-12.23), but there were no improvements in child vocalizations (mean z score, −0.13; 95% CI, −0.49 to 0.24). CONCLUSIONS AND RELEVANCE: A multifaceted clinic-based approach to promote parent-child interactions holds some promise. Future, larger studies are warranted.